Human Papillomavirus Genotypes and its Prevalence in Normal Population: Genotip Human Papillomavirus dan Prevalensinya pada Populasi Normal - Tofan W Utami; Andrijono Andrijono; Laila Nuranna; Darrell Fernando; Alexander AW Peters; Gert J Fleuren; Ekaterina S Jordanova; Sigit Purbadi (Indonesian Journal of Obstetrics and Gynecology, 2014)
Objective: Over 200 types of human papillomavirus (HPV) have been recognized on the basis of DNA sequence. Multiple infection is more prone to be persistent than single infection. The purpose of this study is to assess the variation of HPV types and their prevalence among negative VIA as normal population in Indonesian women. Method: We processed cervical swabs from 1,214 patients with negative VIA. HPV DNA and its genotypes were detected using PCR based INNO-Lipa HPV DNA test. We also classified whether each infection is single or multiple. Result: From 1,214 women with negative VIA, 39 (3.21%) samples were positive for HPV DNA. Among them, we detected 19 types of HPV, consisting of 13 types of high-risk HPV, 5 types of low-risk HPV, and 1 type of unknown HPV (type X). The most prevalent type was HPV type 52 (18.31%), followed by type 39 and X with the same proportion (9.86%), and HPV type 16, 18, and 74 (each 8.45%). Of the total 39 HPV-positive samples, 17 (43.6%) showed multiple-type infection and 22 (56.4%) showed single-type infection. The majority of single infection involves high-risk-HPV. The remaining were type 6, 44, 18, 51 and 66, with each single-type infection showing a prevalence of 4.54%. Conclusion: Our study shows that single HPV infection among the negative VIA population are dominated by high-risk type HPV (types 52, 39, 16, and 18). Single infection was more often encountered than multiple infection. Keywords: HPV DNA, HPV genotypes, multiple infection, negative VIA, single infection